Geologi Wilayah Tapaluluo dan Sekitarnya, Kabupaten Gorontalo - Rasyid, Fajri Fitrah Fidianto A.; Zainuri, Ahmad; Kasim, Muhammad (Journal of Applied Geoscience and Engineering, 2022)
The research area is geographically located at coordinates 0041'30â€ â€“ 0045'00â€ North Latitude and 12300'30â€ â€“ 12303' 35â€ East Longitude with an area of ± 41 Km2. The method used in this research is scientific exploration by conducting a survey of surface geological mapping. It is carried out in the preparation of literature, tools and materials, the data collection stage is in the form of geomorphological data, stratigraphy, geological structure measurements and documentation. The data processing stage is in the form of laboratory analysis, namely conducting petrographic analysis and processing geological structure data in the form of joints and faults using the stereographic method. The geomorphology of the research area is divided into three geomorphological units, namely; lava flow ridge units, intrusion hills, and fault zone hill units. The study area is divided into three rock units informally in order from oldest to youngest, namely: andesite porphyry unit (early-middle Miocene), granodiorite unit (middle-late Miocene), and modified andesite porphyry unit (middle-late Miocene). The geological structure of the study area consists of joints, Tapaluluo Fault, and Botupololondalange Shear Fault. The geological potential of the research area is in the form of mineralization and rock mining.